2009
DOI: 10.1111/j.1460-9568.2009.06650.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient responses from the lateral geniculate nucleus in humans with amblyopia

Abstract: Amblyopia or lazy eye is the most common cause of uniocular blindness in adults. It is caused by a disruption to normal visual development as a consequence of unmatched inputs from the two eyes in early life, arising from a turned eye (strabismus), unequal refractive error (anisometropia) or form deprivation (e.g. cataract). Animal models based on extracellular recordings in anesthetized animals suggest that the earliest site of the anomaly in the primate visual pathway is the primary visual cortex (correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 50 publications
4
120
1
Order By: Relevance
“…This being the case, the model is particularly relevant to V1 as it receives all its input from the LGN and where at the input level the Mand P-inputs from the geniculate are segregated by layer (i.e. 4cB and 4Ca) and have been shown to exhibit reduced responses when driven by the AE [Hess et al, 2009a].…”
Section: Striate Versus Extra-striate Deficitsmentioning
confidence: 99%
“…This being the case, the model is particularly relevant to V1 as it receives all its input from the LGN and where at the input level the Mand P-inputs from the geniculate are segregated by layer (i.e. 4cB and 4Ca) and have been shown to exhibit reduced responses when driven by the AE [Hess et al, 2009a].…”
Section: Striate Versus Extra-striate Deficitsmentioning
confidence: 99%
“…Brain imaging studies with functional Magnetic Resonance Imaging (fMRI) revealed reduced regional cerebral blood flow and blood-oxygen-level dependent (BOLD) response in the lateral geniculate nucleus (Hess et al, 2009), the striate (Barnes et al, 2001;Conner et al, 2007;Demer, 1997;Demer et al, 1988;Kabasakal et al, 1995;Li et al, 2007) and extra-striate cortex (Barnes et al, 2001;Li et al, 2007;Muckli et al, 2006) in amblyopia. There is also a literature from the numerous psychophysical studies that have been carried out on humans with amblyopia where striate and extra-striate cortical processing anomalies have been inferred.…”
Section: Introductionmentioning
confidence: 99%
“…3 Early in the visual pathway, the lateral geniculate nucleus (LGN) shows reduced activation when driven by the amblyopic compared with the fellow eye. 4,5 Downstream from the LGN, reduced activation has also been found in the primary visual cortex (V1), [6][7][8][9] as well as in highorder cortical areas involved in face perception, 10 multiobject tracking, 11 and visual-guided actions. 12 In addition to changes in neural responses, structural neuroimaging has helped us understand the biological underpinnings of the behavioral differences in terms of changes in the structure of either grey matter [13][14][15][16][17][18][19] or white matter.…”
mentioning
confidence: 99%